NIR Spectroscopy of Star-Forming Galaxies at z similar to 1.4 with Subaru/FMOS: The Mass-Metallicity Relation - Yabe, K; Ohta, K; Iwamuro, F; Yuma, S; Akiyama, M; Tamura, N; Kimura, M; Takato, N; Moritani, Y; Sumiyoshi, M; Maihara, T; Silverman, J; et al. (Astronomical Society of Japan, 2012)
We present near-infrared spectroscopic observations of star-forming galaxies at z ∼ 1.4 with FMOS on the Subaru Telescope. We observed K-band selected galaxies in the SXDS/UDS fields with K ≤ 23.9mag, 1.2 ≤ zph ≤ 1.6,M ≥ 10 9.5M, and expected F(Hα) ≥ 10 -16 erg s -1cm -2; 71 objects in the sample have significant detections of H?. For these objects, excluding possible AGNs, identified from the BPT diagram, gas-phase metallicities were obtained from the [N II] /Hα line ratio. The sample is split into three stellar-mass bins, and the spectra are stacked in each stellar-mass bin. The mass-metallicity relation obtained at z ∼ 1.4 is located between those at z ∼ 0.8 and z ∼ 2.2. We constrain the intrinsic scatter to be ∼0.1 dex, or larger in the mass-metallicity relation at z ∼ 1.4; the scatter may be larger at higher redshifts. We found trends that the deviation from the mass-metallicity relation depends on the SFR (Star-formation rate) and the half light radius: Galaxies with higher SFR and larger half light radii show lower metallicities at a given stellar mass. One possible scenario for the trends is the infall of pristine gas accreted from IGM, or through merger events. Our data points show larger scatter than the fundamental metallicity relation (FMR) at z ∼ 0.1, and the averagemetallicities slightly deviate fromthe FMR. The compilation of themass- metallicity relations at z ∼ 3 to z ∼ 0.1 shows that they evolve smoothly from z ∼ 3 to z ∼ 0 without changing the shape so much, except for the massive part at z ∼ 0. © 2012 Astronomical Society of Japan.